Fertility variability in a Latosol cultivated with fertigated banana - de Araújo de Oliveira, Barbemile (Revista Ciência Agronômica, 2021)
Banana production requires strategies to assess the variability of fertigation areas since production can be reduced by consecutive cultivation in chemically-restricted soils and at different elevations. From this perspective, this study aimed to investigate the spatial variability of soil chemical attributes and the soil carbon stock and relate these parameters to the elevation of a banana plantation fertigated by a micro-sprinkler system. The study was conducted at the Irrigation Perimeter Nupeba (Riachão das Neves/BA), in an area cultivated with the banana cultivar Prata for 18 years. In April 2017, single soil samples were collected in an area with a minimum elevation of 440.6 m and a maximum of 445.8 m, at the depths of 0-0.20 m and 0.20-0.40 m, with a sampling grid composed of 40 georeferenced points and spaced 10 meters. The following parameters were determined: pH, total organic carbon (COT), soil organic matter (OM), nitrogen (N), phosphorus (P), potassium (K+ ), calcium (Ca2+), magnesium (Mg2+), aluminum (Al3+), potential acidity (H+Al), sum of bases (SB), cation exchange capacity (CEC), base saturation (V%), and carbon stock (Est C). The data were evaluated by descriptive statistics and geostatistics and showed normal distribution. There was spatial variability, allowing the construction of fertility maps. The maps showed that the elevation especially infl uences the OM, COT, N, and Est C, also showing the distribution and concentration of nutrients in the soil, allowing to minimize the variability through the application of varied nutrient contents aiming at their homogeneous supply to banana plants.